Hair Technique Salon Management System Using Mobile Application - Beh, Jun Yang; Ibrahim, Rosziati (Applied Information Technology And Computer Science, 2021)
Hair Technique Salon Management System is a mobile application that provides a mobile platform that enables customers to make an appointment for hair services and employer and employees to manage the salon’s information and customer’s information. The Hair Technique Salon is currently managing the salon and customer information manually by using paper-based and electronic document management. In addition, it has poor appointment management which only allows customers to make an appointment via phone call. Thus, a mobile-based Hair Technique Salon Management System is developed to solve these inconveniences. In terms of methodology, simple Software Development Life Cycle (SDLC) methodology is used in this project. In this project, the Dart programming language will be used as a mobile-based scripting language, and this application is developed using Flutter, Android Studio and Firebase database. Through this Hair Technique Salon Management System, customer can view salon information, make an appointment, and receive a notification. At the same time, the employer and employees can manage the appointment, manage the salon information, and manage notification easily. The developed system will help improve the hair salon's systematic work management efficiency and expand the customer's segments and increase the hair salon's competitiveness among its peers.